A red mud-based perovskite / carbon nitride composite photocatalyst, a preparation method and application thereof
Patent Information
- Application Number
- CN202611439319.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-30
AI Technical Summary
[0002]氧化铝工业生产过程会产生大量强碱性工业固废赤泥,国内赤泥综合利用率不足5%,绝大多数采用露天堆存方式处置,长期堆放会占用大量土地资源,且赤泥内含氟化物、微量放射性组分,经雨水淋溶后易造成周边土壤、地下水持续性污染,如何实现赤泥低成本高值化利用是铝工业领域亟待解决的难题
1、本发明提供的复合光催化剂采用固废赤泥掺杂调控钙钛矿能带,100min内盐酸多西环素降解率可达95.7%,且复合光催化剂颗粒均匀分布,粒径稳定在21-26nm,两相形成紧密异质结,有效抑制光生电子-空穴复合,活性自由基产量显著提高;
Smart Images

Figure CN122999256A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite photocatalyst technology, and in particular to a red mud-based perovskite / carbon nitride composite photocatalyst, its preparation method, and its application. Background Technology
[0002] The alumina industry generates a large amount of highly alkaline industrial solid waste, red mud. In China, the comprehensive utilization rate of red mud is less than 5%, with the vast majority disposed of through open-air storage. Long-term storage occupies significant land resources. Furthermore, red mud contains fluorides and trace amounts of radioactive components, which, after being leached by rainwater, easily cause continuous pollution of surrounding soil and groundwater. Achieving low-cost, high-value utilization of red mud is a pressing problem for the aluminum industry. Meanwhile, the pharmaceutical and aquaculture industries use large quantities of tetracycline antibiotics such as doxycycline hydrochloride. This pollutant has a stable chemical structure and can persist in aquatic environments for extended periods. Continuous accumulation can induce drug resistance in pathogens and foster superbugs. Conventional water treatment processes are insufficient for complete degradation, necessitating green and efficient water pollution control technologies.
[0003] Currently, photocatalytic oxidation technology, with its advantages of room-temperature reaction, utilization of solar energy, and non-selective mineralization of organic pollutants, has become the mainstream approach for treating antibiotic wastewater. Perovskite LaFeO3 is a classic visible-light-responsive photocatalyst with a band gap of 2.0-2.2 eV and excellent redox performance, widely used in research on the degradation of organic pollutants. Graphite-phase carbon nitride (g-C3N4) is simple to prepare and uses inexpensive raw materials, making it a popular non-metallic visible-light photocatalyst. However, both single catalytic materials have significant drawbacks: pure LaFeO3 is synthesized using high-purity iron and lanthanum salts, resulting in high raw material costs, and its photogenerated electron-hole recombination rate is fast, leading to extremely low catalytic activity. Pure g-C3N4 has a band gap of 2.7 eV, weak visible-light capture ability, poor carrier separation efficiency, and its removal efficiency for doxycycline hydrochloride is less than 4% when used alone.
[0004] To address the shortcomings of single-component catalysis, existing research has focused on preparing LaFeO3 / g-C3N4 heterojunction composite catalysts through physical blending and calcination, relying on two-phase band matching to improve carrier separation efficiency. However, all existing composite systems utilize high-purity chemical reagents to prepare LaFeO3, failing to incorporate industrial solid waste to reduce raw material costs and simultaneously address the pollution problem caused by red mud stockpiles. In the research of red mud-based catalytic materials, existing schemes mostly combine red mud with titanium dioxide, biochar, and simple metal oxides, primarily for application in photo-Fenton and persulfate activation systems. Red mud is rarely used as an iron source to synthesize perovskite-type catalytic materials. Currently, a complete technology for the visible light degradation of tetracycline antibiotics using red mud-based LaFeO3 and g-C3N4 composites has not yet emerged.
[0005] The core defects and causes of existing technologies are as follows: The high cost of raw materials for synthesizing LaFeO3 using high-purity reagents makes large-scale engineering applications difficult; there is a lack of preparation methods to replace high-purity iron sources with industrial solid waste; and the two major problems of solid waste pollution and high catalyst costs cannot be solved simultaneously. Traditional LaFeO3 / g-C3N4 composite systems lack red mud components to regulate the band gap, resulting in a large band gap, a narrow visible light absorption range, and severe photogenerated electron-hole recombination. The degradation rate of doxycycline hydrochloride is only 48.5% within 100 minutes, indicating low treatment efficiency. Conventional red mud-modified catalytic materials only utilize the adsorption properties of red mud, failing to integrate the abundant iron components within the red mud into the perovskite lattice. This prevents optimization of optical performance through lattice regulation, resulting in low added value from red mud resource utilization. Existing composite catalysts exhibit weak interphase interactions, involving only simple physical mixing. The heterojunction charge transport channels are incomplete, leading to limited free radical generation and difficulty in completely mineralizing stable tetracycline antibiotic molecules. Summary of the Invention
[0006] The purpose of this invention is to provide a red mud-based perovskite / carbon nitride composite photocatalyst, its preparation method, and its application. This method utilizes waste red mud to significantly reduce the catalyst preparation cost and eliminate the environmental risks associated with red mud storage, while also enabling efficient degradation of doxycycline hydrochloride wastewater under visible light conditions.
[0007] To achieve the above objectives, the present invention provides a red mud-based perovskite / carbon nitride composite photocatalyst, comprising 5-25% g-C3N4 and the balance red mud-based perovskite by mass percentage, using industrial solid waste red mud as the iron source for synthesizing red mud-based perovskite, and g-C3N4 and red mud-based perovskite uniformly interpenetrating to form a tightly bonded heterojunction interface.
[0008] Preferably, the composite photocatalyst has a particle size of 21-26 nm and a band gap of 2-3 eV.
[0009] A method for preparing a red mud-based perovskite / carbon nitride composite photocatalyst includes the following steps: S1. Heat melamine to 500-600℃ and calcine for 4-5 hours. After natural cooling, grind it thoroughly to obtain g-C3N4 powder. Store it in a light-proof, sealed container for later use. S2. Mix pretreated industrial solid waste red mud, lanthanum nitrate hexahydrate and deionized water, stir evenly, add complexing agent, and continue stirring to obtain a uniform and transparent complexing solution. S3. Heat the complexing liquid in S2 in an oil bath and stir continuously until the complexing liquid can be drawn into continuous fine filaments. After natural cooling, the metal precursor gel is obtained. After drying and dehydration, it is cooled and ground to obtain dry powder. S4. The dry powder in S3 is calcined in stages, then cooled to below 100°C and ground to obtain red mud-based perovskite powder. S5. Mix the red mud-based perovskite powder in S4 and the g-C3N4 powder in S1, grind them thoroughly, heat them at 4-6℃ / min, calcine them at a constant temperature, cool them naturally, and then grind them to obtain the composite photocatalyst.
[0010] Preferably, in S1, the heating rate is 1-5℃ / min.
[0011] Preferably, in S2, the mass ratio of pretreated industrial solid waste red mud, lanthanum nitrate hexahydrate, and complexing agent is 1:2.3-2.7:2-2.5; Complexing agents include one or more of citric acid, ethylene glycol, and tartaric acid.
[0012] Preferably, in S2, the stirring rate is 150-250 r / min and the stirring time is 20-150 min.
[0013] Preferably, in step S3, the oil bath heating temperature is 70-90℃, the drying temperature is 90-120℃, and the drying time is 1-3 hours.
[0014] Preferably, in S4, the segmented calcination involves first holding at 250-350℃ for 20-40 minutes, and then raising the temperature at 4-6℃ / min to 550-650℃ and holding at that temperature for 7-9 hours.
[0015] Preferably, in S5, the constant temperature calcination temperature is 500-600℃, and the constant temperature calcination time is 1-3h.
[0016] An application of a red mud-based perovskite / carbon nitride composite photocatalyst for the degradation of wastewater containing tetracycline antibiotics.
[0017] Mechanism of the invention: Under visible light irradiation, both red mud-based perovskite powder and g-C3N4 powder can simultaneously absorb light energy and generate photogenerated electron-hole pairs. Electrons spontaneously migrate to the conduction band of g-C3N4, while holes remain stably in the valence band of red mud-based perovskite, achieving effective separation of charge carriers. Electrons that migrate to the surface of the composite photocatalyst combine with dissolved oxygen in the water to generate superoxide radicals (O2). - The valence band hole oxidizes water molecules to generate hydroxyl radicals ·OH. These two non-selective strong oxidizing free radicals can gradually destroy the stable structures of the benzene ring and amide bond within the doxycycline hydrochloride molecule, ultimately completely mineralizing organic pollutants into carbon dioxide, water, and harmless inorganic ions.
[0018] Therefore, the present invention employs the above-mentioned red mud-based perovskite / carbon nitride composite photocatalyst, its preparation method, and its application, the beneficial effects of which are as follows: 1. The composite photocatalyst provided by the present invention uses solid waste red mud doping to regulate the perovskite energy band. The degradation rate of doxycycline hydrochloride can reach 95.7% within 100 min. Moreover, the composite photocatalyst particles are uniformly distributed with a stable particle size of 21-26 nm. The two phases form a tight heterojunction, which effectively inhibits the recombination of photogenerated electrons and holes and significantly improves the yield of active free radicals. 2. This invention completely replaces high-purity iron salts with alumina solid waste red mud as the iron source, saving the purchase cost of expensive chemical iron reagents, eliminating the need for high pressure and special reaction equipment, and making the process simple and easy to scale up. It is suitable for small and medium-sized water treatment enterprises to produce in batches, while also utilizing stockpiled red mud and saving the disposal costs of red mud land, seepage prevention, and seepage prevention operation and maintenance. 3. The preparation method provided by this invention has controllable steps, the material structure is stable and free of impurities, and the molecular-level material mixing is achieved by using the sol-gel method, combined with a segmented calcination process, which can generate complete orthorhombic LaFeO3 perovskite; different ratios of red mud-based LaFeO3 perovskite powder and g-C3N4 can stably synthesize composite photocatalysts, with only gradient differences in degradation efficiency, and the process has high fault tolerance; FT-IR and XRD characterization confirmed that no new impurity crystal phases are generated after compositing, and there is a strong interaction between the two phase interfaces, and the obtained composite photocatalyst has good chemical stability; 4. The composite photocatalyst provided by this invention has mild reaction conditions when used for wastewater degradation, and can be carried out at room temperature and pressure. It relies solely on visible light to drive the reaction, without the need to add high-valence oxidizing agents such as hydrogen peroxide and ozone. The reaction products are only CO2, H2O and harmless inorganic ions, without producing toxic halogenated or aromatic byproducts. The composite photocatalyst can be recovered by centrifugation, has the potential for recycling, and reduces the cost of continuous agent addition.
[0019] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0020] Figure 1 These are the infrared spectra of the composite photocatalysts in Examples 1-5 of this invention; Figure 2 These are the XRD patterns of the composite photocatalysts in Examples 1-5 of this invention; Figure 3 This is a combination diagram of the band gap widths of the composite catalysts in Examples 1-5, Comparative Examples 1 and 3-6, and the red mud-based perovskite powder in Comparative Example 2 and Example 1. Figure 3 In the diagram, 'a' represents the band gap width of the red mud-based perovskite powders in Comparative Example 2 and Example 1. Figure 3 In the diagram, b represents the band gap width of the composite catalysts in Example 2 and Comparative Example 3. Figure 3 In the diagram, 'c' represents the band gap of the composite catalysts in Example 5 and Comparative Example 6. Figure 3In the diagram, d represents the band gap width of the composite catalysts in Example 1 and Comparative Example 1. Figure 3 In the diagram, 'e' represents the band gap width of the composite catalysts in Example 3 and Comparative Example 4. Figure 3 f in the figure represents the band gap width of the composite catalysts in Example 4 and Comparative Example 5; Figure 4 These are SEM images of the composite photocatalyst at different magnification levels in Example 1. Figure 4 In the image, 'a' represents the SEM image magnified 200,000 times. Figure 4 In the image, b represents the SEM image magnified 100,000 times. Figure 4 In the image, 'c' represents the SEM image magnified 50,000 times. Figure 4 In the image, d represents the SEM image magnified 20,000 times. Figure 4 In the image, 'e' represents the SEM image magnified 10,000 times. Figure 4 In the image, f represents the SEM image magnified 0.5 times. Figure 5 The graphs show the performance of comparative examples 1-6 and g-C3N4 powder in degrading doxycycline hydrochloride wastewater. Figure 6 These are performance graphs of red mud-based perovskite powder and g-C3N4 powder in Examples 1-5, showing their degradation of doxycycline hydrochloride wastewater. Figure 7 The graphs show the performance of Example 1 and Comparative Example 1 in degrading doxycycline hydrochloride wastewater. Detailed Implementation
[0021] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.
[0022] This invention provides a red mud-based perovskite / carbon nitride composite photocatalyst, comprising 5-25% g-C3N4 and the balance red mud-based LaFeO3 perovskite by mass percentage. Industrial solid waste red mud is used as the iron source for synthesizing the red mud-based perovskite, and carbon nitride g-C3N4 and red mud-based perovskite are uniformly interwoven to form a tightly bonded heterojunction interface.
[0023] In some embodiments of the present invention, the particle size of the composite photocatalyst is 21-26 nm and the band gap is 2-3 eV.
[0024] A method for preparing a red mud-based perovskite / carbon nitride composite photocatalyst includes the following steps: S1. Melamine is heated to 500-600℃ and calcined for 4-5 hours. After natural cooling, it is ground thoroughly to obtain g-C3N4 powder, which is stored in a light-proof and sealed container for later use. A non-metallic semiconductor substrate with visible light response capability is obtained, which is used to construct a heterojunction with red mud-based perovskite.
[0025] S2. Mix pretreated industrial solid waste red mud, lanthanum nitrate hexahydrate, and deionized water. After stirring evenly, add a complexing agent and continue stirring to obtain a homogeneous and transparent complexing solution. The complexing agent reacts with the Fe dissolved in the red mud. 3+ And the added La 3+ Complexation is performed to achieve uniform mixing at the molecular level, locking metal ions uniformly in the complexing solution and preventing them from precipitating separately due to hydrolysis during subsequent heating.
[0026] S3. Heat the complexing liquid in S2 in an oil bath and stir continuously until the complexing liquid can be drawn into continuous fine filaments. After natural cooling, a metal precursor gel is obtained. After drying and dehydration, it is cooled and ground to obtain a dry powder. Oil bath heating promotes the slow evaporation of water, and the metal-complexing agent complex undergoes esterification and cross-linking polymerization to form a three-dimensional network structure of metal precursor gel. Drying removes the water inside the metal precursor gel, and the volume shrinkage produces micropores. The metal ions in the dry powder obtained by grinding still maintain an atomic-level uniform distribution.
[0027] S4. The dry powder in S3 is calcined in stages, then cooled to below 100℃ and ground to obtain red mud-based perovskite powder. The red mud-based perovskite powder is red mud-based LaFeO3 perovskite powder. The iron, aluminum and silicon metal oxides naturally contained in the red mud of alumina industrial solid waste can be uniformly doped into the LaFeO3 perovskite lattice, and the perovskite band structure is reconstructed by the metal ions contained in the red mud of alumina industrial solid waste.
[0028] S5. The red mud-based perovskite powder from S4 and the g-C3N4 powder from S1 are mixed and thoroughly ground. After heating at 4-6℃ / min, the mixture is calcined at a constant temperature, naturally cooled, and then ground again to obtain the composite photocatalyst. The g-C3N4 powder and the red mud-based perovskite form a heterojunction charge transport channel, which effectively inhibits the recombination behavior of photogenerated electrons and holes, and increases the total amount of highly oxidizing free radicals generated in the system.
[0029] In some embodiments of the present invention, in S1, the heating rate is 1-5°C / min. Slow heating ensures uniform heating of the melamine molecules and avoids localized overheating that could lead to precursor boiling or carbonization.
[0030] In some embodiments of the present invention, in S2, the pretreatment of industrial solid waste red mud is as follows: the weighed red mud is placed in a nitric acid solution with a concentration of 0.5-1 mol / L and heated for 2 hours, then filtered, washed until neutral and dried, placed in a crucible, and then heated to 350°C in a muffle furnace at a heating rate of 5°C / min and kept at a constant temperature for 2 hours. After the high-temperature treatment is completed, the sample is allowed to cool naturally to room temperature in the furnace, thus completing the activation pretreatment of the red mud.
[0031] In some embodiments of the present invention, in S2, the mass ratio of pretreated industrial solid waste red mud, lanthanum nitrate hexahydrate and complexing agent is 1:2.3-2.7:2-2.5; Complexing agents include one or more of citric acid, ethylene glycol, and tartaric acid.
[0032] In some embodiments of the present invention, in S2, the stirring rate is 150-250 r / min and the stirring time is 20-150 min.
[0033] In some embodiments of the present invention, in step S3, the oil bath heating temperature is 70-90°C, the drying temperature is 90-120°C, and the drying time is 1-3 hours.
[0034] In some embodiments of the present invention, in step S4, the segmented calcination involves first holding the gel at 250-350°C for 20-40 minutes to decompose and remove the complexing organic ligands and residual nitrate ions in the dry gel. Then, the temperature is increased to 550-650°C at a rate of 4-6°C / min and held at that temperature for 7-9 hours. This segmented high-temperature calcination can drive a solid-state reaction between lanthanum and iron ions, generating a structurally complete ABO3-type perovskite crystal phase.
[0035] In some embodiments of the present invention, in step S5, the isothermal calcination temperature is 500-600℃, and the isothermal calcination time is 1-3 hours. This can strengthen the interfacial bonding force between the two phases, shorten the carrier migration path, and ensure that photogenerated electrons can rapidly migrate across the interface to the g-C3N4 conduction band, thus constructing a stable and efficient carrier transport channel.
[0036] An application of a red mud-based perovskite / carbon nitride composite photocatalyst for the degradation of wastewater containing tetracycline antibiotics.
[0037] In some embodiments of the present invention, the wastewater containing tetracycline antibiotics is doxycycline hydrochloride wastewater. During degradation, visible light or a 300W high-pressure xenon lamp is used as an energy source to excite the catalyst to generate active charge carriers.
[0038] Example 1 S1. Place 5g of analytical grade melamine into an alumina crucible, heat it in a muffle furnace to 550℃ at 3℃ / min for 4.5h, and then grind it thoroughly after cooling to room temperature to obtain a light yellow g-C3N4 powder. Store it in a sealed container away from light for later use.
[0039] S2. Mix 2.0086g of pretreated industrial solid waste red mud, 5.0431g of lanthanum nitrate hexahydrate and 50mL of deionized water, stir at 200r / min for 30min until the mixture is uniform, add 4.2069g of complexing agent citric acid, and continue stirring at 200r / min for 2h to obtain a uniform and transparent complexing solution.
[0040] S3. Place the complexing solution from S2 into a beaker and heat it in an 80°C oil bath. Cover the mouth of the beaker with plastic wrap with two small holes to control the rate of water evaporation. Continue stirring until the complexing solution can be drawn into continuous fine filaments of 1-2 cm. After natural cooling for 10 minutes, the metal precursor gel is obtained. Dry it in a hot air drying oven at 100°C for 2 hours to dehydrate it, then cool and grind it to obtain a dry powder.
[0041] S4. The dry powder in S3 is calcined in stages. First, it is kept at 300℃ for 30 minutes, then the temperature is increased to 600℃ at 5℃ / min and kept at 600℃ for 8 hours. After cooling to below 100℃, it is taken out and ground to obtain reddish-brown red mud-based LaFeO3 perovskite powder (lanthanum ferrite in red mud).
[0042] S5. Mix 8.5g of red mud-based perovskite powder from S4 and 1.5g of g-C3N4 powder from S1 (15% carbon nitride / lanthanum ferrite from red mud), and grind thoroughly. Transfer to a crucible and place in a muffle furnace. Heat to 550℃ at 5℃ / min and calcine at a constant temperature for 2 hours. After natural cooling, grind to obtain the composite photocatalyst.
[0043] Example 2 S1. Place 5g of analytical grade melamine into an alumina crucible, heat it in a muffle furnace to 550℃ at 3℃ / min for 4.5h, and then grind it thoroughly after cooling to room temperature to obtain a light yellow g-C3N4 powder. Store it in a sealed container away from light for later use.
[0044] S2. Mix 2.0086g of pretreated industrial solid waste red mud, 5.0431g of lanthanum nitrate hexahydrate and 50mL of deionized water, stir at 200r / min for 30min until the mixture is uniform, add 4.2069g of complexing agent citric acid, and continue stirring at 200r / min for 2h to obtain a uniform and transparent complexing solution.
[0045] S3. Place the complexing solution from S2 into a beaker and heat it in an 80°C oil bath. Cover the mouth of the beaker with plastic wrap with two small holes to control the rate of water evaporation. Continue stirring until the complexing solution can be drawn into continuous fine filaments of 1-2 cm. After natural cooling for 10 minutes, the metal precursor gel is obtained. Dry it in a hot air drying oven at 100°C for 2 hours to dehydrate it, then cool and grind it to obtain a dry powder.
[0046] S4. The dry powder in S3 is calcined in stages. First, it is kept at 300℃ for 30 minutes, then the temperature is increased to 600℃ at 5℃ / min and kept at 600℃ for 8 hours. After cooling to below 100℃, it is taken out and ground to obtain reddish-brown red mud-based LaFeO3 perovskite powder (lanthanum ferrite in red mud).
[0047] S5. Mix 9.5g of red mud-based perovskite powder from S4 and 0.5g of g-C3N4 powder from S1 (5% carbon nitride / lanthanum ferrite from red mud) and grind them thoroughly. Transfer the mixture to a crucible and place it in a muffle furnace. Heat the mixture to 550℃ at a rate of 5℃ / min and calcine it at that temperature for 2 hours. After natural cooling, grind the mixture to obtain the composite photocatalyst.
[0048] Example 3 S1. Place 5g of analytical grade melamine into an alumina crucible, heat it in a muffle furnace to 550℃ at 3℃ / min for 4.5h, and then grind it thoroughly after cooling to room temperature to obtain a light yellow g-C3N4 powder. Store it in a sealed container away from light for later use.
[0049] S2. Mix 2.0086g of pretreated industrial solid waste red mud, 5.0431g of lanthanum nitrate hexahydrate and 50mL of deionized water, stir at 200r / min for 30min until the mixture is uniform, add 4.2069g of complexing agent citric acid, and continue stirring at 200r / min for 2h to obtain a uniform and transparent complexing solution.
[0050] S3. Place the complexing solution from S2 into a beaker and heat it in an 80°C oil bath. Cover the mouth of the beaker with plastic wrap with two small holes to control the rate of water evaporation. Continue stirring until the complexing solution can be drawn into continuous fine filaments of 1-2 cm. After natural cooling for 10 minutes, the metal precursor gel is obtained. Dry it in a hot air drying oven at 100°C for 2 hours to dehydrate it, then cool and grind it to obtain a dry powder.
[0051] S4. The dry powder in S3 is calcined in stages. First, it is kept at 300℃ for 30 minutes, then the temperature is increased to 600℃ at 5℃ / min and kept at 600℃ for 8 hours. After cooling to below 100℃, it is taken out and ground to obtain reddish-brown red mud-based LaFeO3 perovskite powder (lanthanum ferrite in red mud).
[0052] S5. Mix 8.0g of red mud-based perovskite powder from S4 and 2.0g of g-C3N4 powder from S1 (20% carbon nitride / lanthanum ferrite from red mud) and grind them thoroughly. Transfer the mixture to a crucible and place it in a muffle furnace. Heat the mixture to 550℃ at a rate of 5℃ / min and calcine it at this temperature for 2 hours. After natural cooling, grind the mixture to obtain the composite photocatalyst.
[0053] Example 4 S1. Place 5g of analytical grade melamine into an alumina crucible, heat it in a muffle furnace to 550℃ at 3℃ / min for 4.5h, and then grind it thoroughly after cooling to room temperature to obtain a light yellow g-C3N4 powder. Store it in a sealed container away from light for later use.
[0054] S2. Mix 2.0086g of pretreated industrial solid waste red mud, 5.0431g of lanthanum nitrate hexahydrate and 50mL of deionized water, stir at 200r / min for 30min until the mixture is uniform, add 4.2069g of complexing agent citric acid, and continue stirring at 200r / min for 2h to obtain a uniform and transparent complexing solution.
[0055] S3. Place the complexing solution from S2 into a beaker and heat it in an 80°C oil bath. Cover the mouth of the beaker with plastic wrap with two small holes to control the rate of water evaporation. Continue stirring until the complexing solution can be drawn into continuous fine filaments of 1-2 cm. After natural cooling for 10 minutes, the metal precursor gel is obtained. Dry it in a hot air drying oven at 100°C for 2 hours to dehydrate it, then cool and grind it to obtain a dry powder.
[0056] S4. The dry powder in S3 is calcined in stages. First, it is kept at 300℃ for 30 minutes, then the temperature is increased to 600℃ at 5℃ / min and kept at 600℃ for 8 hours. After cooling to below 100℃, it is taken out and ground to obtain reddish-brown red mud-based LaFeO3 perovskite powder (lanthanum ferrite in red mud).
[0057] S5. Mix 7.5g of red mud-based perovskite powder from S4 and 2.5g of g-C3N4 powder from S1 (25% carbon nitride / lanthanum ferrite from red mud), and grind thoroughly. Transfer to a crucible and place in a muffle furnace. Heat to 550℃ at 5℃ / min and calcine at a constant temperature for 2 hours. After natural cooling, grind to obtain the composite photocatalyst.
[0058] Example 5 S1. Place 5g of analytical grade melamine into an alumina crucible, heat it in a muffle furnace to 550℃ at 3℃ / min for 4.5h, and then grind it thoroughly after cooling to room temperature to obtain a light yellow g-C3N4 powder. Store it in a sealed container away from light for later use.
[0059] S2. Mix 2.0086g of pretreated industrial solid waste red mud, 5.0431g of lanthanum nitrate hexahydrate and 50mL of deionized water, stir at 200r / min for 30min until the mixture is uniform, add 4.2069g of complexing agent citric acid, and continue stirring at 200r / min for 2h to obtain a uniform and transparent complexing solution.
[0060] S3. Place the complexing solution from S2 into a beaker and heat it in an 80°C oil bath. Cover the mouth of the beaker with plastic wrap with two small holes to control the rate of water evaporation. Continue stirring until the complexing solution can be drawn into continuous fine filaments of 1-2 cm. After natural cooling for 10 minutes, the metal precursor gel is obtained. Dry it in a hot air drying oven at 100°C for 2 hours to dehydrate it, then cool and grind it to obtain a dry powder.
[0061] S4. The dry powder in S3 is calcined in stages. First, it is kept at 300℃ for 30 minutes, then the temperature is increased to 600℃ at 5℃ / min and kept at 600℃ for 8 hours. After cooling to below 100℃, it is taken out and ground to obtain reddish-brown red mud-based LaFeO3 perovskite powder (lanthanum ferrite in red mud).
[0062] S5. Mix 9.0g of red mud-based perovskite powder from S4 and 1.0g of g-C3N4 powder from S1 (10% carbon nitride / lanthanum ferrite from red mud), and grind thoroughly. Transfer to a crucible and place in a muffle furnace. Heat to 550℃ at 5℃ / min and calcine at a constant temperature for 2 hours. After natural cooling, grind to obtain the composite photocatalyst.
[0063] Example 6 Accurately weigh 60 mg of analytical grade doxycycline hydrochloride, dissolve it in deionized water, and dilute to 1 L to obtain doxycycline hydrochloride wastewater with a concentration of 60 mg / L. Pour 60 mL of the doxycycline hydrochloride wastewater into a photocatalytic reaction vessel, add 0.03 g of the composite photocatalyst prepared in Example 1, and stir magnetically for 30 min under light-protected conditions to allow the composite photocatalyst and pollutants to reach adsorption-desorption equilibrium, eliminating the interference of simple adsorption on the photocatalytic degradation results.
[0064] A 300W high-pressure xenon lamp was used to simulate a visible light environment, and the reaction was continued for 100 minutes. The degradation rate of doxycycline hydrochloride was 95.7%. The pseudo-first-order kinetic rate constant k = 0.02172 min. -1 After the reaction is completed, the solid catalyst and the treated water are separated by centrifugation. The doxycycline hydrochloride in the water has been completely mineralized. The separated and recovered catalyst can be reused for recycling after washing and drying.
[0065] Comparative Example 1 The difference between this comparative example and Example 1 is that in S2, equimolar analytically pure ferric nitrate was used to replace the pretreated industrial solid waste red mud (15% carbon nitride / lanthanum ferrite), while the rest of the steps were the same as in Example 1, to obtain the composite photocatalyst.
[0066] Comparative Example 2 S1. Mix 4.6996g of analytical grade ferric nitrate, 5.0431g of lanthanum nitrate hexahydrate and 50mL of deionized water, stir at 200r / min for 30min until the mixture is homogeneous, add 4.2069g of complexing agent citric acid, and continue stirring at 200r / min for 2h to obtain a homogeneous and transparent complexing solution.
[0067] S2. Place the complexing solution from S1 into a beaker and heat it in an 80°C oil bath. Cover the mouth of the beaker with plastic wrap with two small holes to control the rate of water evaporation. Continue stirring until the complexing solution can be drawn into continuous fine filaments of 1-2 cm. After natural cooling for 10 minutes, the metal precursor gel is obtained. Dry it in a hot air drying oven at 100°C for 2 hours to dehydrate it, then cool and grind it to obtain a dry powder.
[0068] S3. The dry powder in S2 is calcined in stages. First, it is kept at 300℃ for 30 minutes, then the temperature is increased to 600℃ at 5℃ / min and kept at 600℃ for 8 hours. After cooling to below 100℃, it is taken out and ground to obtain pure phase lanthanum ferrite LaFeO3 powder.
[0069] Comparative Example 3 The difference between this comparative example and Example 2 is that in S2, equimolar analytically pure ferric nitrate was used to replace the pretreated industrial solid waste red mud (5% carbon nitride / lanthanum ferrite), while the rest of the steps were the same as in Example 1, to obtain the composite photocatalyst.
[0070] Comparative Example 4 The difference between this comparative example and Example 3 is that in S2, equimolar analytically pure ferric nitrate was used to replace the pretreated industrial solid waste red mud (20% carbon nitride / lanthanum ferrite), while the rest of the steps were the same as in Example 1, to obtain the composite photocatalyst.
[0071] Comparative Example 5 The difference between this comparative example and Example 4 is that in S2, equimolar analytically pure ferric nitrate was used to replace the pretreated industrial solid waste red mud (25% carbon nitride / lanthanum ferrite), while the rest of the steps were the same as in Example 1, to obtain the composite photocatalyst.
[0072] Comparative Example 6 The difference between this comparative example and Example 5 is that in S2, equimolar analytically pure ferric nitrate was used to replace the pretreated industrial solid waste red mud (10% carbon nitride / lanthanum ferrite), while the rest of the steps were the same as in Example 1, to obtain the composite photocatalyst.
[0073] Comparative Example 7 The difference between this comparative example and Example 6 is that the composite photocatalyst in Comparative Example 1 is used, while the rest of the steps are the same as in Example 6. The degradation rate of doxycycline hydrochloride in 100 min is only 48.5%.
[0074] Comparative Example 8 The difference between this comparative example and Example 6 is that the pure phase LaFeO3 powder from Comparative Example 2 was used, while the rest of the steps were the same as in Example 6. The degradation rate of doxycycline hydrochloride was only 2.3% after 100 min.
[0075] Comparative Example 9 The difference between this comparative example and Example 6 is that g-C3N4 powder was used, while the rest of the steps were the same as in Example 6. The degradation rate of doxycycline hydrochloride was only 3.5% after 100 min.
[0076] Performance testing a. Infrared spectroscopy tests were performed on the composite photocatalysts in Examples 1-5, and the results are as follows: Figure 1 As shown, the composite photocatalysts in Examples 1-5 exhibit a high performance at 549 cm⁻¹. -1 There is a distinct absorption peak for the Fe-O bond stretching vibration, which is a characteristic vibration of the FeO6 octahedron in the lanthanum ferrite lattice; simultaneously, the catalyst shows an absorption peak at 1631 cm⁻¹. -1 There is a characteristic absorption peak at 807 cm⁻¹, corresponding to the stretching vibration of the conjugated C=N double bond. -1 The peak at that point represents the characteristic breathing vibration of the triazine ring. This indicates that the characteristic peaks of lanthanum ferrite and carbon nitride in red mud were simultaneously retained in Examples 1-5.
[0077] b. XRD tests were performed on the composite photocatalysts in Examples 1-5, and the results are as follows: Figure 2 As shown, the peak positions of the composite photocatalysts in Examples 1-5 are basically consistent with those of the orthorhombic lanthanum ferrite standard card. With the increasing proportion of carbon nitride, the diffraction signal corresponding to the carbon nitride crystal plane at 2θ=27.4° gradually increases, but no obvious independent sharp diffraction peak is formed. This is mainly because carbon nitride is uniformly dispersed in the system, and its diffraction signal is covered by the high-intensity characteristic peaks of red mud lanthanum ferrite. No new impurity diffraction peaks were generated in the composite photocatalysts of Examples 1-5.
[0078] c. The composite photocatalysts from Examples 1-5 were dispersed in ethanol to obtain a uniform suspension. After ultrasonic oscillation for 30 min, the absorption spectrum was measured using a UV-Vis spectrophotometer, and the resulting band gap was calculated. Figure 3As shown. The band gap of pure lanthanum ferrite in Comparative Example 2 is 2.39 eV, and the band gap of red mud-based perovskite powder in Example 1 is 2.20 eV. The band gaps of the composite photocatalysts in Examples 2, 5, 1, 3, and 4 are 2.92 eV, 2.82 eV, 2.31 eV, 2.49 eV, and 2.61 eV, respectively. The band gaps of the composite photocatalysts in Comparative Examples 3, 6, 1, 4, and 5 are 2.23 eV, 2.31 eV, 2.09 eV, 2.44 eV, and 2.58 eV, respectively.
[0079] The comparison of the above data shows that the band gaps of Examples 1-5 are all lower than those of Comparative Examples 1 and 3-6. This means that Examples 1-5 containing red mud have a better response to visible light and also have superior photocatalytic activity.
[0080] d. The composite photocatalyst in Example 1 was tested by scanning electron microscopy, such as... Figure 4 As shown, the composite photocatalyst particles have a particle size range of 21-26 nm, are uniformly distributed, and have a tight matrix bond.
[0081] e. The composite photocatalysts from Examples 1-5, Comparative Example 1, Comparative Examples 3-6, and the pure-phase lanthanum ferrite LaFeO3 powder from Comparative Example 2, the red mud-based perovskite powder from Example 1, and g-C3N4 powder were used to treat doxycycline hydrochloride wastewater using the degradation method described in Example 6. The results are as follows: Figure 5 and Figure 6 As shown, the degradation efficiency of the composite photocatalysts in Examples 2-5 and Comparative Example 1 is higher than that of the pure phase lanthanum ferrite LaFeO3 powder in Comparative Example 2. Furthermore, the degradation efficiency of the composite photocatalysts in Examples 2-5, Comparative Examples 3-6, and Comparative Example 1 shows a trend of first increasing and then decreasing with the increase of g-C3N4 powder.
[0082] The composite photocatalyst in Example 1 exhibited the highest degradation efficiency, with a (C / CO) ratio dropping to approximately 0.043 after 100 minutes of illumination. The composite photocatalysts in Example 5 and Example 2 had (C / CO) ratios of approximately 0.061 and 0.071, respectively, after 100 minutes of illumination. The red mud-based perovskite powder in Example 1 had a (C / CO) ratio of approximately 0.104, while the g-C3N4 powder showed the weakest self-degradation ability, with a (C / CO) ratio close to 0.965. The composite photocatalysts in Examples 3 and 4 showed a decrease in effectiveness, with (C / CO) ratios of approximately 0.146 and 0.167, respectively.
[0083] Figure 7It can be seen that, compared with Comparative Example 1, the introduction of pretreated industrial solid waste red mud as an iron source in Example 1 can significantly improve the photocatalytic degradation activity of the composite photocatalyst for doxycycline hydrochloride.
[0084] Therefore, this invention employs the above-mentioned red mud-based perovskite / carbon nitride composite photocatalyst, its preparation method, and its application. The composite photocatalyst uses solid waste red mud doping to regulate the perovskite energy band, achieving a doxycycline hydrochloride degradation rate of 95.7% within 100 minutes. Furthermore, the composite photocatalyst particles are uniformly distributed with a stable particle size of 21-26 nm, forming a tight heterojunction between the two phases, effectively suppressing photogenerated electron-hole recombination and significantly increasing the yield of active free radicals.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A red mud-based perovskite / carbon nitride composite photocatalyst, characterized in that: The mixture comprises 5-25% g-C3N4 and the balance red mud-based perovskite by mass percentage. Industrial solid waste red mud is used as the iron source for synthesizing red mud-based perovskite. g-C3N4 and red mud-based perovskite are uniformly interwoven to form a tightly bonded heterojunction interface.
2. The red mud-based perovskite / carbon nitride composite photocatalyst according to claim 1, characterized in that: The composite photocatalyst has a particle size of 21-26 nm and a band gap of 2-3 eV.
3. A method for preparing a red mud-based perovskite / carbon nitride composite photocatalyst, characterized in that: The preparation of the composite photocatalyst as described in any one of claims 1-2 comprises the following steps: S1. Heat melamine to 500-600℃ and calcine for 4-5 hours. After natural cooling, grind it thoroughly to obtain g-C3N4 powder. Store it in a light-proof, sealed container for later use. S2. Mix pretreated industrial solid waste red mud, lanthanum nitrate hexahydrate and deionized water, stir evenly, add complexing agent, and continue stirring to obtain a uniform and transparent complexing solution. S3. Heat the complexing liquid in S2 in an oil bath and stir continuously until the complexing liquid can be drawn into continuous fine filaments. After natural cooling, the metal precursor gel is obtained. After drying and dehydration, it is cooled and ground to obtain dry powder. S4. The dry powder in S3 is calcined in stages, then cooled to below 100°C and ground to obtain red mud-based perovskite powder. S5. Mix the red mud-based perovskite powder in S4 and the g-C3N4 powder in S1, grind them thoroughly, heat them at 4-6℃ / min, calcine them at a constant temperature, cool them naturally, and then grind them to obtain the composite photocatalyst.
4. The method for preparing a red mud-based perovskite / carbon nitride composite photocatalyst according to claim 3, characterized in that: In S1, the heating rate is 1-5℃ / min.
5. The method for preparing a red mud-based perovskite / carbon nitride composite photocatalyst according to claim 3, characterized in that: In S2, the mass ratio of pretreated industrial solid waste red mud, lanthanum nitrate hexahydrate, and complexing agent is 1:2.3-2.7:2-2.5; Complexing agents include one or more of citric acid, ethylene glycol, and tartaric acid.
6. The method for preparing a red mud-based perovskite / carbon nitride composite photocatalyst according to claim 3, characterized in that: In S2, the stirring rate is 150-250 r / min and the stirring time is 20-150 min.
7. The method for preparing a red mud-based perovskite / carbon nitride composite photocatalyst according to claim 3, characterized in that: In S3, the oil bath heating temperature is 70-90℃, the drying temperature is 90-120℃, and the drying time is 1-3 hours.
8. The method for preparing a red mud-based perovskite / carbon nitride composite photocatalyst according to claim 3, characterized in that: In S4, the segmented calcination involves first holding the temperature at 250-350℃ for 20-40 minutes, and then raising the temperature at 4-6℃ / min to 550-650℃ and holding it at that temperature for 7-9 hours.
9. The method for preparing a red mud-based perovskite / carbon nitride composite photocatalyst according to claim 3, characterized in that: In S5, the constant temperature calcination temperature is 500-600℃, and the constant temperature calcination time is 1-3h.
10. The application of a red mud-based perovskite / carbon nitride composite photocatalyst, characterized in that: The composite photocatalyst as described in any one of claims 1-2 is applied to the degradation of wastewater containing tetracycline antibiotics.
